PENGARUH PROFESIONALISME DAN ETIKA TERHADAP PERTIMBANGAN MATERIALITAS DALAM PENGAUDITAN LAPORAN KEUANGAN (Students' Journal of Accounting and Banking, 2012)
The purpose of this study was to obtain empirical evidence about the influence of professionalism and ethics of the profession of public accounting materiality level considerations in the process of examination of financial statements.The population in this study is the auditor who worked in Public Accounting Firm (KAP) in Semarang and Solo. Sample selection method used is non-probability sampling technique, which is purposive sampling. Obtained samples of 34 respondents. Data analysis technique used is multiple linea regression analysis.The results of this study can be concluded that: (1) professionalism in a positive effect on the level of materiality considerations in the process of auditing the financial tatements. (2) professional ethics in a positive effect on the level of materiality considerations in the process of auditing thefinancial statements.Keywords: professionalism, professional ethics and onsideration of the materiality of public accountants